The Effectiveness of Strength Based Counseling Model to Improve Academic Hope in Students - Dody Hartanto; Sunaryo Kartadinata; Ilfiandra Ilfiandra; Ahman Ahman (Universitas Ahmad Dahlan, 2020)
This study aims to determine the effectiveness of the self-strength counseling model in developing student academic expectations. The study was conducted using a single-subject experimental design to measure the relationship between 2 variables, namely self-strength counseling and academic expectations. The type of design used is the A-B-A design, where there are three experimental phases, namely phase A is the baseline phase and phase B is the intervention phase. The data analysis used in this research is descriptive statistical techniques because the study has a single case (single subject). The number of subjects in this study was limited, namely only five students. The results showed that self-strength counseling was effective in increasing student academic expectations after the intervention process. The study results can be used to reference counselors in higher education to improve student academic expectations through the self-strength counseling model.